Students Counselling Guidance Using Digital Platforms and Satisfaction for Online Learning - Asriyanti Rosmalina (Journal of Innovation in Educational and Cultural Research, 2023)
The study aimed to obtain an analysis of the use of digital platforms and the level of satisfaction through student prospects during dare learning which has been carried out for 2 years at the State Islamic Institute of Sheikh Nurjati Cirebon. This study was designed using mixed methods, namely qualitative and quantitative methods. The participants in this study were students of the Faculty of Ushuluddin Adab and Da'wah of Institute Agama Islam Negeri Syekh Nurjati Cirebon with a total of 758 students. They are students in the even semester of the 2020-2021 and 2021-2022 academic years. Data collection was carried out using a questionnaire distributed to participants, observations and documents. The data obtained were analyzed using quantitative data analysis using MS Excel. For the qualitative analysis, the inductive coding technique was used. The results of the data analysis found two main conclusions, namely, first, the use of digital platforms is related to digital competence, and the level of student motivation and responsibility is lower. Meanwhile, the online learning environment and digital technology facilities are quite good. The second conclusion is the level of satisfaction which shows students are dissatisfied with the aspects of interaction, evaluation, communication, and the usefulness of online learning. The results of these findings also recommend that teachers pay attention to the level of needs, abilities, and readiness of students in carrying out online learning.